2023
DOI: 10.1101/2023.07.10.23292473
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparing frequency of booster vaccination to prevent severe COVID-19 by risk group in the United States

Abstract: While waning protection from vaccination and natural infection against SARS-CoV-2 infection is well-documented, recent analyses have also found waning of protection against severe COVID-19. This highlights a broader need to understand the optimal timing of COVID-19 booster vaccines specific to an individual to mitigate the risk of severe COVID-19, while accounting for waning of protection and differential risk by age group and immune status. Here we show that more frequent COVID-19 booster vaccination (every 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Booster vaccination has tremendous public health potential (20,42,43). However, uptake of COVID-19 booster vaccination by low proportions of residents has lowered its public health impact (26).…”
Section: Discussionmentioning
confidence: 99%
“…Booster vaccination has tremendous public health potential (20,42,43). However, uptake of COVID-19 booster vaccination by low proportions of residents has lowered its public health impact (26).…”
Section: Discussionmentioning
confidence: 99%
“…However, the estimation of the magnitude and durability of protection through COVID-19 vaccination has become a challenge because of the emergence of the omicron variants which altered virus characteristics, such as transmissibility and antigenicity, evolving in response to herd immunity 9 . A recent study reported that frequent COVID-19 booster vaccination in older age groups and the immunocompromised population would effectively reduce the burden of severe COVID-19 by analyzing COVID-19 surveillance and seroprevalence data 10 .…”
Section: Introductionmentioning
confidence: 99%